Gearless Micro Hydropower Plant for Small Water-course; XXXII. Kandó Konferencia 2016. Kandó a tudomány hajóján - Dementiev Yu. N. Yuriy Nikolaevich; Kuzmin R. V. Roman Vladimirovich; Serikov A. L. Andrey Leonidovich; Suzdorf V. I. Viktor Ivanovich; Obraztsov K. V. Konstantin Valentinovich; Negodin K. N. Kirill Nikolaevich; Fedorova I. B. Irina Borisovna (Automation Section, 2016)
Title screen